2000
DOI: 10.1190/1.1444872
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and seismic imaging of massive sulfides

Abstract: Laboratory studies show that the acoustic impedances of massive sulfides can be predicted from the physical properties (V p , density) and modal abundances of common sulfide minerals using simple mixing relations. Most sulfides have significantly higher impedances than silicate rocks, implying that seismic reflection techniques can be used directly for base metals exploration, provided the deposits meet the geometric constraints required for detection. To test this concept, a series of 1-, 2-, and 3-D seismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…For example, Noranda Inc. (now Xstrata) acquired several post-Lithoprobe 2D and 3D seismic data sets for VHMS exploration in the Bathurst and Abitibi mining camps. One of the best-known surveys acquired by Noranda is the Halfmile Lake 3D survey (New Brunswick) that led to the discovery of a 6-8 Mt massive sulfide lens at a depth of 1.2 km (Figure 9; Salisbury et al, 2000;Matthews, 2002;Malehmir and Bellefleur, 2009). Similar 3D surveys in the Sudbury complex also were successful in delineating massive sulfide deposits (see Milkereit et al, 2000).…”
Section: Canadamentioning
confidence: 99%
“…For example, Noranda Inc. (now Xstrata) acquired several post-Lithoprobe 2D and 3D seismic data sets for VHMS exploration in the Bathurst and Abitibi mining camps. One of the best-known surveys acquired by Noranda is the Halfmile Lake 3D survey (New Brunswick) that led to the discovery of a 6-8 Mt massive sulfide lens at a depth of 1.2 km (Figure 9; Salisbury et al, 2000;Matthews, 2002;Malehmir and Bellefleur, 2009). Similar 3D surveys in the Sudbury complex also were successful in delineating massive sulfide deposits (see Milkereit et al, 2000).…”
Section: Canadamentioning
confidence: 99%
“…If this interpretation of continuation of the Vilminko Formation and Kuuhkamo deposit is correct, the reflections at the end of the seismic profile V3 at 600-1200 m depth (200-400 ms, CMP 1800-2200) are interesting for exploration because of their high amplitude, indicating anomalous values of acoustic impedances. Typically, sulfide minerals have significantly higher acoustic impedance than their host rocks (Salisbury et al, 2000). L'Heureux et al (2009) concluded that the scattering nature of the background has an important effect on detection of massive sulfides as does the size and shape of the deposit.…”
Section: Geological Interpretation Of Seismic Datamentioning
confidence: 99%
“…Looking at Figure 11b, a negative relationship between the P-wave velocity and sulfide content even can be imagined. Pyrrhotite is a major component of the sulfide mineralogy, and pyrrhotite is known to have a negative effect on seismic velocities (see Salisbury et al, 2000;Malehmir et al, 2012). Therefore, a slight decrease in the seismic velocity where sulfide content increases can be expected in the Kevitsa area.…”
Section: Exploration Targetsmentioning
confidence: 99%
“…To our knowledge, there is no 3D reflection seismic survey conducted for deep open-pit mine planning. Three-and twodimensional reflection seismic surveys have, however, been used for the exploration of deep-seated mineral deposits with several examples from Canada, South Africa, Europe, and Australia (e.g., Milkereit et al, 1996Milkereit et al, , 2000Salisbury et al, 2000;Adam et al, 2003;Pretorius et al, 2003;Malehmir et al, 2007Malehmir et al, , 2009aMalehmir et al, , 2009bMalehmir et al, , 2011Harrison and Urosevic, 2009;Bellefleur, 2009, 2010;Dehghannejad et al, 2010Dehghannejad et al, , 2012Cheraghi et al, 2011;Juhojuntti et al, 2012). Kevitsa, our study area, is a large nickel/copper deposit hosted by a massive ultramafic intrusion in northern Finland (Figure 1) with measured and indicated resources of 240 million tons (using a nickel cutoff grade of 0.1%) grading 0.30% nickel and 0.41% copper.…”
Section: Introductionmentioning
confidence: 99%